Everyday violence: the public harassment of women and LGBTQ people - Kolysh, Simone (Rutgers University Press, 2021)
"Everyday Violence is based on ten years of scholarly rage against catcalling and aggression directed at women and Lesbian, Gay, Bisexual, Transgender and Queer (LGBTQ) people of New York City. Simone Kolysh recasts public harassment as everyday violence and demands an immediate end to this pervasive social problem. Analyzing interviews with initiators and recipients of everyday violence through an intersectional lens, Kolysh argues that gender and sexuality, shaped by race, class, and space, are violent processes that are reproduced through these interactions in the public sphere. They examine short and long-term impacts and make inroads in urban sociology, queer and trans geographies, and feminist thought. Kolysh also draws a connection between public harassment, gentrification, and police brutality resisting criminalizing narratives in favor of restorative justice. Through this work, they hope for a future where women and LGBTQ people can live on their own terms, free from violence"--